Case of penetrating orbitocranial injury caused by wood. Issue 6 (June 1991) - Mutlukan, E; Fleck, B W; Cullen, J F; Whittle, I R
Abstract : A case of retained intraorbital and intracerebral wooden foreign body following an orbitocranial penetrating injury through the lower lid of an adult is described. Initial failure to recognise the true nature of the injury led to intracerebral abscess formation and monocular blindness. Diagnosis and management of such cases are discussed.